A phase I study of the safety and efficacy of talimogene laherparepvec in Japanese patients with advanced melanoma. Issue 8 (30th June 2022) - Yamazaki, Naoya; Isei, Taiki; Kiyohara, Yoshio; Koga, Hiroshi; Kojima, Takashi; Takenouchi, Tatsuya; Yokota, Kenji; Namikawa, Kenjiro; Yi, Min; Keegan, Alissa; Fukushima, Satoshi
Abstract: Talimogene laherparepvec (T‐VEC) is approved for the treatment of unresectable melanoma in the USA, Europe, and Australia. This phase I, multicenter, open‐label, dose de‐escalation study evaluated the safety and efficacy of T‐VEC in Japanese patients with unresectable stage IIIB–IV melanoma. Eligible adult patients had histologically confirmed stage IIIB–IVM1c cutaneous melanoma, may have received prior systemic anticancer therapy, must have had ≥1 injectable lesion, serum lactate dehydrogenase ≤1.5x upper limit of normal, ECOG performance status of 0 or 1, and adequate hematologic, hepatic, and renal function. T‐VEC was injected intralesionally (first dose, ≤4.0 ml of 10 6  PFU/ml; after 3 weeks and then every 2 weeks thereafter, ≤4.0 ml of 10 8  PFU/ml). Primary endpoints were dose‐limiting toxicities (DLTs) and durable response rate (DRR). Of 18 enrolled patients (72.2% female), 16 had received ≥1 prior line of therapy. Ten patients discontinued T‐VEC due to disease progression. Median (range) follow‐up was 20.0 (4–37) months. No DLTs were observed; 17 (94.4%) patients had treatment‐emergent adverse events (AEs). Fourteen (77.8%) patients had treatment‐related AEs; the most frequent were pyrexia (44.4%), malaise (16.7%), chills, decreased appetite, pruritus, and skin ulcer (11.1% each). The primary efficacy endpoint was met: 2 (11.1%) patients had a durable partial response ≥6 months. The DRR was consistent with that observed in a phase III trial of T‐VEC in non‐Asian patients. The safety profile was consistent with the patients' underlying disease and the known safety profile of T‐VEC. Abstract : This phase I study assessed the safety and efficacy of talimogene laherparepvec (T‐VEC) in Japanese patients with advanced melanoma including rare subtypes. The safety profile was similar to previous reports of T‐VEC monotherapy, and the durable response rate was consistent with that observed in non‐Asian patients.